Vertical sorting within dune structure - Abdel-Motaleb, Mohamed M. M., author; Gessler, Johannes, advisor; Molinas, Albert, committee member; Richardson, E. V., committee member; Zachmann, D. W., committee member (Colorado State University. Libraries, 1993)
Vertical sorting of sediment mixtures within dune structures was measured experimentally by conducting three types of experiments: running water experiments, still water experiments, and air experiments. Five different sediment mixtures with known initial gradations were used. The median grain diameters for the five sediment mixtures were between 0.35 mm and 0.86 mm, the geometric standard deviations of the same sediment mixtures were between 2.30 and 2.9. In the running water experiments, each experiment was continued until the dunes were fully developed down the flume. Then each dune was sampled along several horizontal layers. In the still water experiments, a delta shape was deposited, foreset by foreset, following one another in a continuous way. In the air experiments, the sand mixture was deposited as in the still water experiments. These experiments were to study the effect of the gravitational force on the vertical sorting process. The results of the running water experiments showed clearly demonstrated the vertical sorting process (vertical reduction in the sediment grain diameter) within the two-dimensional dunes. Also, the still water and air experiments showed the importance of the hydrodynamic force on the sorting process. A prediction equation relating the median grain diameter within the dune structure in the vertical direction to the back flow velocity on the lee face of the dune and the submerged weight of the sediment particle was used to calculate the vertical median grain diameter for the two-dimensional dune and compared with the measured data. Five dimensionless parameters were tested to correct the error in the predicted values. The dimensionless grain diameter gave the best result. Other sets of laboratory and field data for a point bar and three-dimensional dunes showed the sorting phenomenon. Calculated values for the vertical median grain diameter for the three-dimensional dune computed using the prediction equation agreed reasonably well with the observed values.
Keywords: Sediment transport; Bed load; Sedimentation and deposition